Analysis of Working Capital in Relation With Income of the Small Weaving Industry in Kupang City - Wehelmina M Ndoen (Riset Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study aims to determine whether working capital has an effect on the income of the Small Weaving Industry in Kupang City. Methodology/approach: This study used a quantitative descriptive approach. This research was conducted in the Small Weaving Industry in Kupang City, which has a total population of 49 weavers. Saturated samples were obtained. Data collection methods included questionnaires, interviews, documentation, and observation. The data analysis technique uses financial theory related to working capital and income. Results/findings: The results showed that working capital has an effect on the income of small industrial weavers in Kupang City because the greater the amount of working capital spent, the greater the income earned. Therefore, it is recommended that weavers maintain working capital conditions so that the production process can be increased by itself and the income will increase. Conclusions: Working capital is a significant factor influencing the income of small weaving industry actors. Maintaining adequate capital levels can directly support higher productivity and revenue. Limitations: The study is limited to a single city and industry type, so results may not be generalized to other sectors or regions. Contribution: This study provides empirical evidence on the relationship between working capital and income in the small industry sector, useful for policymakers and microenterprise development programs.